Analysis of Students' Analytical Thinking Ability and Mathematical Communication Using Online Group Investigation Learning Model - Jihan Azizah Al-Hanifah; Yus Mochamad Cholily; Siti Khoiruli Ummah (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
Analytical thinking and mathematical communication are abilities included in the learning process objectives. This study aims to describe students' analytical thinking skills and mathematical communication using the online group investigation cooperative learning model. The subjects of this research were 30 students of class VIII-C. The type of research used is descriptive qualitative. The data to determine the implementation of learning and the ability to think analytically and communicate mathematically are observations, documentation, and tests. The study results show that the online group investigation type cooperative learning model implementation takes place following the steps of group investigation learning. The results of the ability to think analytically and communicate mathematically meet all indicators. The distinguishing indicator of analytical thinking ability is the most widely achieved, and the one that has yet to be completed much is the attributing indicator. So that students' analytical thinking skills have an analytical category. The most widely conducted indicator of mathematical communication ability is the indicator of expressing mathematical ideas in writing. What has yet to be widely achieved is the indicator of analyzing and evaluating mathematical concepts. So that students' mathematical communication skills have a mathematical category.